Treatment non-compliance and government aided health schemes : a boon or a curse - Manjula M.V.; Y.S. Pawar (International Journal of Medical Research and Review, 2019)
Purpose: In this study we tried to analyze the prevalence of non-adherence to radiation treatment, the factors behind the unplanned breaks and the evaluation of strategies to overcome such breaks.Materials and Methods: Between January 2017 to October 2017, 486 patients were registered for radical radiotherapy of which 91 patients with unplanned treatment break were identified. We analyzed the social, economic, educational, and therapeutic barriers that led to treatment interruptions.Results: 91 patients of 486 patients registered for radical radiotherapy with unplanned treatment break were identified. The age of such patients ranged from 30 to 85 years with a median age of 52.5 years. 61 were males and 30 were females. 39 patients were from urban areas and 52 belonged to rural area. Of these 91 patients 85 patients were receiving cashless treatment based on BPL cards and 6 were cash paying patients. 52 Patients had Head and neck, 23 had gynecological, 7 with breast and 4 patients had esophageal cancers. Majority of patients in our study had treatment breaks during the mid to end phase of a radical radiotherapy schedule with the onset of Grade II or III acute reactions.Conclusion: As majority of patients were supported by government schemes without any binding factor, some compelling factors like blocking the BPL cards to avail other benefits, or to impose some kind of penalties to avoid wastage of government efforts and resources.